Pengaruh Kepemimpinan, Iklim Organisasi, dan Karakteristik Individu Terhadap Kinerja Pengurus Koperasi di Martapura Kalimantan Selatan - Kadir, Abdul (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2020)
The purpose of this study was to examine and analyze the effect of leadership, organizational climate, and individual characteristics on the performance of cooperative management in Martapura, South Kalimantan. This research was conducted on cooperative managers in Martapura, South Kalimantan, where the population was all cooperative managers. The population in this study amounted to 148 cooperative managers, while the sample taken in this study was 71 respondents. The validity of the questionnaire was tested by using the Pearson Product Moment correlation method, while the reliability test of the questionnaire used the Cronbach Alpha method. The data analysis technique was carried out using the Multiple Linear Regression method. Based on the research results and data analysis, it was concluded that; (1) simultaneously the variables of leadership, organizational climate, individual characteristics affect the performance of cooperative management in Martapura, South Kalimantan at an error rate of 5%. The three variables, namely leadership, organizational climate and individual characteristics together are able to contribute 76% to changes in the performance of cooperatives in Martapura, South Kalimantan, while the remaining 24% is the contribution of other variables not observed in this study, (2) leadership partially influences the performance of cooperative management in Martapura, South Kalimantan. The contribution of organizational climate to the performance of cooperative management in Martapura, South Kalimantan is 57%. Leadership affects the performance of cooperative management in Martapura, South Kalimantan by 68.6%. Individual characteristics affect the performance of cooperative administrators in Martapura, South Kalimantan by 28.1%, (3) the most dominant variable affecting cooperative management in Martapura South Kalimantan is leadership, because it has the highest standardized coefficients beta value of 0.546 compared to the value of standardized coefficients beta variable. another free.